Pengaruh Motivasi Terhadap Hasil Belajar Dribbling Permainan Bola Basket - Rendra Agung Prabowo; I Putu Agus Dharma Hita; Fatimah Malini Lubis; Siti Patimah; Eskawida Eskawida; Siska Siska (Journal on Education, 2023)
Learning outcomes play a very important role in the teaching and learning process as they can be used as a standard to measure the extent of changes that occur in students after receiving learning experiences that can be observed and measured through the knowledge, attitudes, and skills they acquire. This study aims to determine the influence of motivation on the learning outcomes of dribbling in basketball. This study uses a correlational research design with a simple regression technique. The study was conducted at Triatma Mulya University with a sample size of 16 students in the Primary School Teacher Education Program. The data collection technique for the level of motivation in this study uses a questionnaire, while the learning outcomes are measured using the skills score in the Physical Education course with dribbling basketball material. The results of this study show that learning motivation has a positive influence on the learning outcomes of dribbling basketball material by 86.8%.